1993
DOI: 10.1007/bf00399086
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal insulin secretion and glucose metabolism in pancreatic islets from the spontaneously diabetic GK rat

Abstract: Insulin secretion and islet glucose metabolism were compared in pancreatic islets isolated from GK/Wistar (GK) rats with spontaneous Type 2 (non-insulin-dependent) diabetes mellitus and control Wistar rats. Islet insulin content was 24.5 +/- 3.1 microU/ng islet DNA in GK rats and 28.8 +/- 2.5 microU/ng islet DNA in control rats, with a mean (+/- SEM) islet DNA content of 17.3 +/- 1.7 and 26.5 +/- 3.4 ng (p < 0.05), respectively. Basal insulin secretion at 3.3 mmol/l glucose was 0.19 +/- 0.03 microU.ng islet DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
185
5

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(208 citation statements)
references
References 24 publications
18
185
5
Order By: Relevance
“…Other studies using GK rats originating from local colonies have also documented an impaired insulin secretory response [7,8]. Nevertheless it was claimed that such impairment in the London colony was not related to a reduced pancreatic insulin content [8], whereas decreased as well as normal pancreatic insulin content, together with normal islet beta-cell density, have been reported in adult GK rats in the Stockholm colony [7,9,10]. These conflicting data led us to document more extensively the beta-cell mass in GK rats originating from the Paris colony.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other studies using GK rats originating from local colonies have also documented an impaired insulin secretory response [7,8]. Nevertheless it was claimed that such impairment in the London colony was not related to a reduced pancreatic insulin content [8], whereas decreased as well as normal pancreatic insulin content, together with normal islet beta-cell density, have been reported in adult GK rats in the Stockholm colony [7,9,10]. These conflicting data led us to document more extensively the beta-cell mass in GK rats originating from the Paris colony.…”
Section: Discussionmentioning
confidence: 92%
“…Plasma insulin release in vivo in response to intravenous glucose was lacking and in vitro studies of insulin release with isolated perfused pancreas or perifused islets [6] indicated that both early and late phases of glucose-induced insulin release were markedly affected in the adult GK rat. Other studies using GK rats originating from local colonies have also documented an impaired insulin secretory response [7,8]. Nevertheless it was claimed that such impairment in the London colony was not related to a reduced pancreatic insulin content [8], whereas decreased as well as normal pancreatic insulin content, together with normal islet beta-cell density, have been reported in adult GK rats in the Stockholm colony [7,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Several animal models for NIDDM have been described. Although recent studies have revealed impaired insulin secretion in GK rats [5][6][7], most of the animal models for NIDDM are characterized by obesity, hyperinsulinaemia and islet hypertrophy [8].…”
Section: Discussionmentioning
confidence: 99%
“…Several animal models for NIDDM have been described. Although recent studies have revealed impaired insulin secretion in GK rats [5][6][7], most of the animal models for NIDDM are characterized by obesity, hyperinsulinaemia and islet hypertrophy [8].The NSY (Nagoya-Shibata-Yasuda) mouse is a spontaneous model of NIDDM with moderate obesity that was established by selective breeding for glucose intolerance from a non-diabetic JcI:ICR mouse colony [9]. Previous studies suggested that NSY mice develop renal lesions similar to diabetic nephro-…”
mentioning
confidence: 99%
“…GK rats exhibit moderate but enhanced fasting glucose levels, evident from 6 weeks of age, due to decreased beta cell secretion of insulin (Ostenson et al 1993). Also, GK rats present normal lipidemia, peripheral and hepatic insulin resistance, and late complications, such as nephropathy or neuropathy.…”
Section: Introductionmentioning
confidence: 99%